Faktor-Faktor yang Mempengaruhi Pemilihan Kontrasepsi KB Suntik 3 Bulan - Tatik Dwi Yani; Seftiani Wulandari (Inovasi Kesehatan Global, 2024)
Family Planning (KB) is an action that assists individuals or married couples in achieving specific objectives, preventing unwanted pregnancies, spacing pregnancies, controlling the timing of childbirth within marital relationships, and determining the number of children in a family. Injectable contraception is one of the most commonly used pregnancy prevention methods in Indonesia. Factors related to the use of injectable contraceptives include Knowledge, Parity, Husband's Support, and Income. To review the literature on the factors influencing the choice of 3-month injectable contraceptive KB. Method: The method of writing this article is a literature review using Google Scholar. Articles were selected based on open access, full text availability in English and Indonesian published in the last decade (2020–2023). There are 6,750 articles identified and published from 2019-2023. Out of these 6,750 articles, 10 articles meet the inclusion and exclusion criteria. Based on the research findings, the 10 reviewed articles indicate that several factors influence the choice of 3-month injectable hormonal contraception. Based on the literature review conducted on the factors influencing the choice of 3-month injectable hormonal contraception KB, it is influenced by Knowledge, parity, husband's support, and income, with Knowledge being the most dominant factor.